2017
DOI: 10.18632/oncotarget.18892
|View full text |Cite
|
Sign up to set email alerts
|

LINC00052 upregulates EPB41L3 to inhibit migration and invasion of hepatocellular carcinoma by binding miR-452-5p

Abstract: Numerous studies have demonstrated that a class of long noncoding RNAs (lncRNAs) are dysregulated in hepatocellular carcinoma (HCC) and they are closely related with tumorigenesis. Our previous studies indicated that LINC00052 was a downregulated lncRNA in HCC and acted as a tumor suppressor gene. Using transcription microarray analysis, we found that knockdown of LINC00052 resulted in EPB41L3 downregulation. However, the function of EPB41L3 and the mechanism of LINC00052 downregulating EPB41L3 in HCC remain u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 45 publications
0
39
1
Order By: Relevance
“…In our study, the non‐effect of SOX9‐AS1 on the SOX9 promoter and the cytoplasmic expression of SOX9‐AS1 indicated that SOX9‐AS1 might regulate SOX9 at the post‐transcriptional level. An increasing number of studies have revealed that lncRNA could regulate gene expression through sponging miRNA in HCC (Lu et al ., ; Zhu et al ., ). We identified 47 miRNA interacting with both SOX9‐AS1 and SOX9 through bioinformatics tools and picked the five most downregulated miRNA in order to investigate their interaction with SOX9‐AS1.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In our study, the non‐effect of SOX9‐AS1 on the SOX9 promoter and the cytoplasmic expression of SOX9‐AS1 indicated that SOX9‐AS1 might regulate SOX9 at the post‐transcriptional level. An increasing number of studies have revealed that lncRNA could regulate gene expression through sponging miRNA in HCC (Lu et al ., ; Zhu et al ., ). We identified 47 miRNA interacting with both SOX9‐AS1 and SOX9 through bioinformatics tools and picked the five most downregulated miRNA in order to investigate their interaction with SOX9‐AS1.…”
Section: Discussionmentioning
confidence: 97%
“…For example, in HCC, lncRNA NNT‐AS1 promoted progression and metastasis by regulating the miR‐363/CDK6 axis (Lu et al ., ). LINC00052 regulated EPB41L3 by targeting miR‐452‐5p to inhibit HCC (Zhu et al ., ). The miRNA are conserved non‐coding transcripts with about 22 nucleotides, responsible for silencing gene expression through targeting 3′UTR of mRNA (Bartel, ; Brümmer and Hausser, ).…”
Section: Introductionmentioning
confidence: 97%
“…8 Moreover, it could bind to miR-452-5p as a sponge and downregulated its target gene, erythrocyte membrane protein band 4.1 like 3 (EPB41L3), in HCC. 9 In addition to its effects in HCC, researchers found that LINC00052 had a significant effect on gastric cancer and breast cancer. [10][11][12] Despite these findings, LINC00052's function in CRC has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The function of LINC00052 varies depending on the location of tumors. It acts as a tumor suppressor through inhibiting cell proliferation, invasion and migration in hepatocellular carcinoma (Xiong et al 2016;Yan et al 2018;Zhu et al 2017), whereas it could promote breast cancer growth (Salameh et al 2017) and gastric cell metastasis and proliferation (Shan et al 2017).…”
Section: Discussionmentioning
confidence: 99%